The effect of herbicides and surfactants on turf grasses and annual poa - Finlayson, M.P.; Dastgheib, F. (New Zealand Plant Protection, 2000)
The tolerance of browntop (Agrostis capillaris L) perennial ryegrass (Lolium perenne L) Chewings fescue (Festuca nigrescens Lam) and annual poa (Poa annua L) to twelve herbicides with and without two organosilicone surfactants (Silwet L77 and Silwet S800) were assessed Annual poa was controlled by haloxyfop and clethodim plus S800 Browntop was highly tolerant to chlorsulfuron and metsulfuron and Chewings fescue to haloxyfop fluazifop clethodim and sethoxydim Organosilicone surfactants affected the tolerance of some species to certain herbicides For example Silwet L77 reduced the tolerance of annual poa to glyphosate but S800 increased the tolerance of perennial ryegrass to terbuthylazine The results have implications for the management of cool season turf